2023
DOI: 10.3389/fmed.2023.1183886
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of common inflammatory and nutritional indicators before treatment in prognosis evaluation of non-small cell lung cancer: a retrospective real-world study

Abstract: ObjectiveTo evaluate the prognostic value of common clinical inflammatory and nutritional indicators before treatment in patients with non-small cell lung cancer in the real world.MethodA total of 5,239 patients with pathologically confirmed non-small cell lung cancer from 2011 to 2018 in the Affiliated Cancer Hospital of Xinjiang Medical University were selected. Their inflammatory and nutritional indicators (RDW, PDW, NLR, LMR, NMR, PLR, SII, PNI, TP, ALB, CYRFA21-1, CEA, CA125, NSE, α1-globulin, α2-globulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Bo Zhou [24] reviewed 101 patients and found that preoperative NLR ≥ 1.80 is independently associated with lymph node metastases for patients undergoing resection of nonfunctioning pancreatic neuroendocrine tumors. Gorkem Eskiizmir [25] retrospectively analyzed the medical records of patients with benign laryngeal tumors, precancerous lesions, and malignant tumors, and found that there was no signi cant difference in NLR between the three groups, but NLR was a predictor of stage, lymph node metastasis, and distant metastasis. Therefore, they proposed that pretreatment NLR is a useful and reliable marker for predicting lymph node metastasis and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Bo Zhou [24] reviewed 101 patients and found that preoperative NLR ≥ 1.80 is independently associated with lymph node metastases for patients undergoing resection of nonfunctioning pancreatic neuroendocrine tumors. Gorkem Eskiizmir [25] retrospectively analyzed the medical records of patients with benign laryngeal tumors, precancerous lesions, and malignant tumors, and found that there was no signi cant difference in NLR between the three groups, but NLR was a predictor of stage, lymph node metastasis, and distant metastasis. Therefore, they proposed that pretreatment NLR is a useful and reliable marker for predicting lymph node metastasis and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although various studies point out the independent value of certain inflammatory biomarkers to predict overall survival [ 15 , 16 , 17 , 18 ], some state that combined scoring could have a higher predictive potential concerning the prognosis [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%